Determinants of Entrepreneurial Intention Among Millennial Generation - Abdul Majid, Izaidin; Koe, Wei Loon; Ismail, Kamariah; Sa'ari, Juan Rizal (2012)
Entrepreneurs are the "engines of economic growth". They have brought enormous positive contributions to a country's economic growth and social development. Among the contributions are such as innovation and job creation. As entrepreneurship is synonymous with self-employed, it is believed to be an effective strategy in handling the issue of employability, particularly among the youths. Understanding of the factors that predict entrepreneurial intention is crucial because entrepreneurial behavior is a result of intention. Though entrepreneurial intention has been widely studied by scholars from overseas, the question of their applicability in the local setting still remains. To date, intention of young generation, specifically the millennial generation in our country to embark on entrepreneurship continues to be unclear. As such, this conceptual paper proposes a research framework by extending Ajzen's (1991) theory of planned behavior (TPB) to study entrepreneurial intention among millennial generation. Specifically, knowledge, experience and ties are the independent variables; meanwhile, attitude, social norm, perceived behavioral control and personality traits act as the mediating variables.